2020
DOI: 10.3390/molecules25040962
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Rapid Evaporative-Ionization Mass Spectrometry as a Shotgun Approach for the Comprehensive Characterization of Kigelia Africana (Lam) Benth. Fruit

Abstract: Rapid evaporative-ionization mass spectrometry (REIMS) coupled with an electroknife as a sampling device was recently employed in many application fields to obtain a rapid characterization of different samples without any need for extraction or cleanup procedures. In the present research, REIMS was used to obtain a metabolic profiling of the Kigelia africana fruit, thus extending the applicability of such a technique to the investigation of phytochemical constituents. In particular, the advantages of REIMS lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…bacterial colonies [33][34][35] and plant materials [48]. Within a few seconds, the burn event generates a complex, richly detailed mass spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…bacterial colonies [33][34][35] and plant materials [48]. Within a few seconds, the burn event generates a complex, richly detailed mass spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…A mass spectrometric method such as REIMS has compelling advantages in the context of field studies. First, because there is zero sample preparation, the generation of the aerosol can be applied to a broad range of biological material, including tissues, [2729], foodstuffs [3032, 47], faecal pellets [37], bacterial colonies [3335] and plant materials [48]. Within a few seconds, the burn event generates a complex, richly detailed mass spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Principal component analysis revealed that several candidate biomarkers that could be used to distinguish Bronte pistachios from the others that were tested [ 17 ]. REIMS has also been used for biomarker profiling of the Kigelia africana fruit which are of increasing importance for its drug-like properties resulting from numerous secondary metabolites [ 60 ]. The study confirmed the presence of antioxidant molecules such as flavonoids and iridoids, and provided insights into the native lipid composition which may contribute to the biological activity of the fruit [ 60 ].…”
Section: Provenancementioning
confidence: 99%
“…REIMS has also been used for biomarker profiling of the Kigelia africana fruit which are of increasing importance for its drug-like properties resulting from numerous secondary metabolites [ 60 ]. The study confirmed the presence of antioxidant molecules such as flavonoids and iridoids, and provided insights into the native lipid composition which may contribute to the biological activity of the fruit [ 60 ]. Numerous examples of economically motivated fraud have been documented in a wide range of botanicals, particularly herbs and spices [ 61 ].…”
Section: Provenancementioning
confidence: 99%
“…Sumac has also counted as a source of natural dyes for the textile industry, yellow dye coming from young stems, brown from roots, black from leaves, and red from fruits. Especially bark and fruit preparations have been extensively used in popular medicine to obtain natural remedies against different affections such as eye and urinary tract infections, ulcer, diarrhea, and hepatic disorders [ 4 , 6 , 7 ]. Recently, R. coriaria has also gained some interest for its ornamental features that could be of value in urban landscaping and gardening [ 8 ].…”
Section: Introductionmentioning
confidence: 99%